Systemic Antifolate Chemotherapy Does Not Select for Fluconazole-Resistant Candida: A Multicenter Clinical Study - Dawid Żyrek; Joanna Nowicka; Magdalena Pajączkowska; Mariola Paściak; Katarzyna Machnik; Tomasz Werner; Zygmunt Konieczny; Piotr Jędrzejczak; Dominika Raźniewska; Gabriela Fijałkowska; Michał Piątek; Barbara Radecka; et al. (Pathogens)
Previous studies have demonstrated that Candida spp. isolates exposed in vitro to the folic acid antagonist methotrexate may develop multidrug cross-resistance to azole antifungals. The aim of this study was to determine whether systemic therapy with antineoplastic antifolates—pemetrexed or methotrexate—constitutes a risk factor for colonization or infection with fluconazole-resistant yeasts. The study group comprised 44 cancer patients who received high-dose systemic antifolate therapy, while the control group consisted of 48 patients without prior exposure to either methotrexate or pemetrexed. Oral swabs and relevant clinical data were collected from all participants. In total, 109 fungal strains representing 13 species were isolated, identified, and subsequently tested for fluconazole susceptibility. Fluconazole-resistant isolates were identified in 4 out of 44 (9.1%) antifolate-treated patients and in 3 out of 48 (6.3%) control patients. Our findings suggest that, although this phenomenon occurs in vitro, systemic antineoplastic antifolate therapy does not induce azole resistance among endogenous yeast species in vivo.